1855 Ill. Laws, 25, An Act To Incorporate the Town of Daville, § 16 - (:unkn) unknown (General Publisher, 1855)
Granted the town of Daville the power and authority to regulate the storage of tar, pitch, rosin, gun powder, and other combustible materials.
--
Keywords: GUN POWDER STORAGE